Developing the Social Studies Curriculum at the Primary Stage in View of the Standards of the Next Generation (Journal Of Educational and Psychological Researches, 2023)
The aim of the current research is to develop the social studies curriculum at the primary stage in light of the standards of the next generation, which was represented in three main dimensions (pivotal ideas, scientific practices, and comprehensive concepts). The researcher designed a tool for the study, which is a content analysis card in the light of (NGSS) standards, based on the previous main dimensions. The descriptive analytical approach was adopted in analyzing the social studies curriculum for the primary stage to determine the degree to which the standards of the next generation are available, as well as to establish the theoretical framework related to the research variables. To develop the social studies curriculum in light of the standards of the next generation